SCHOOL CULTURE IN BUILDING CHARACTER AT SMA NEGERI 5 KUPANG - Vitalia Imul (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2023)
This study uses a descriptive qualitative method, namely research that obtains descriptive information in written and oral form which is obtained directly from the people being observed. The research subjects were school principals, teachers, students, and security officers. The data collection techniques are observation, interviews, and documentation. Data analysis is divided into four parts, namely data collection, data reduction, data display, and conclusions drawing/verifying. The results of the study show that in schools there are religious characters, polite characters, disciplined characters, clean, tidy and beautiful carried out through a civilizing process, although there is still some unconsciousness among school members in obeying and carrying out the values that are already in effect at school. The role of the Principal of SMA Negeri 5 Kupang in building the character of the school community is to run all programs in the school such as supervision, managerial and entrepreneurship.